Nexus between Performance Appraisal Practices and Career Development of Employees in Nepalese Commercial Banks - Pant, Bandana (Nepalese Journal of Management, 2025)
This study examines the nexus between performance appraisal practices and career development of employees in Nepalese commercial banks. Career development is the dependent variable. The selected independent variables are comprehensive feedback system, training and development programs, mentoring and coaching programs, reward and promotion system, and career and succession planning. The primary source of data is used to assess the opinions of respondents regarding comprehensive feedback system, training and development programs, mentoring and coaching programs, reward and promotion system, career and succession planning, and career development. The study is based on primary data of 103 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of performance appraisal practices on career development of employees in Nepalese commercial banks. The study showed a positive impact of a comprehensive feedback system on career development. It indicates that an effective comprehensive feedback system leads to increase in career development. Similarly, the study showed a positive impact of training and development programs on career development. It indicates that training and development programs lead to the increase in career development. Likewise, the study also revealed a positive impact of mentoring and coaching programs on career development. It indicates that mentoring and coaching programs lead to an increase in career development. Further, the study observed a positive impact of a reward and promotion system on career development. It indicates that an effective reward and promotion system leads to an increase in career development. In addition, the study observed a positive impact of career and succession planning on career development. It indicates that effective career and succession planning leads to an increase in career development.